A case of pulmonary veno-occlusive disease: diagnostic dilemmas and therapeutic challenges. (April 2013) - Sourla, Evdokia; Paspala, Asimina; Boutou, Afroditi; Kontou, Paschalina; Stanopoulos, Ioannis; Pitsiou, Georgia
Pulmonary veno-occlusive disease (PVOD) is a rare cause of pulmonary hypertension (PH). Misdiagnosis of the disease is common since PVOD presents with clinical and radiographic features mimicking idiopathic pulmonary arterial hypertension or even PH due to interstitial lung disease. Vasodilators may not be efficacious in PVOD and may in fact worsen hemodynamic status with the development of pulmonary edema. Lung transplantation represents the best treatment option. In the present report we describe the challenging diagnosis of PVOD in a patient with PH referred to our department. Final diagnosis was established by surgical lung biopsy. The patient was offered sequential combination therapy under close monitoring and maintained remarkable clinical stabilization while being on the waiting list for lung transplantation.